Answer:
x = -3 x = 2
Explanation:
![2x^(2) + 2x - 12 = 0\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/deemmh6talkp4yq5tx1kol4fg6ruai5721.png)
First divide every term by 2.
![2x^(2) + 2x - 12 = 0\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/deemmh6talkp4yq5tx1kol4fg6ruai5721.png)
/2 /2 /2 /2
It now simplifies to...
![x^(2) + x - 6 = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/ikxi5qjt038nqvfijy016s86b49q2v0ul0.png)
Now you have to find 2 values that multiply to -6 and add to 1.
These numbers are 3 and -2
(x + 3)(x - 2) = 0
Now make a T-chart or separate both terms and equal them to 0 and solve.
x + 3 = 0 x - 2 = 0
x = -3 x = 2
Plug both values in the original equation one at a time and check if the equation equals zero.